Attention and syntax in sentence production: A critical review - Andriy Myachykov; Simon Garrod; Christoph Scheepers (Discours)
People often speak about visually perceived events that unfold in real time. In doing so speakers regularly translate the details of the visual world they describe onto the grammatical properties of the sentences about it. For example, the speaker needs to map her constantly changing attentional state onto the syntactic plan of the produced sentences. The present paper briefly discusses what attention is, explores methods for the co-activation of attentional and syntactic operations during the production of visually-mediated sentences in languages with different syntactic properties, and reviews the evidence for a regular link between the speaker’s choice of sentential structure and the distribution of the speaker’s attention to the event’s referents. Also, it discusses evidence for interactive properties of attentional and other types of priming on the speaker’s syntactic choice. Based on reviewed literature, we conclude that attention plays a crucial role in directing lexical and grammatical choices in human discourse. At the same time, the organization of the language’s grammar reciprocates this influence by constraining the extent to which the distribution of attention can affect the real-time syntactic choices. Finally, we discuss how attentional priming engages in complex interactions with other priming effects: it interacts with lexical priming but not with syntactic priming, supporting an encapsulated view of sentence formulation.